Lower cerebrospinal fluid/plasma fibroblast growth factor 21 (FGF21) ratios and placental FGF21 production in gestational diabetes. - Bee K Tan; Kavitha Sivakumar; Muhammad F Bari; Manu Vatish; Harpal S Randeva (PLoS ONE, 2013)
OBJECTIVES: Circulating Fibroblast Growth Factor 21 (FGF21) levels are increased in insulin resistant states such as obesity, type 2 diabetes mellitus and gestational diabetes mellitus (GDM). In addition, GDM is associated with serious maternal and fetal complications. We sought to study human cerebrospinal fluid (CSF) and corresponding circulating FGF21 levels in women with gestational diabetes mellitus (GDM) and in age and BMI matched control subjects. We also assessed FGF21 secretion from GDM and control human placental explants. DESIGN: CSF and corresponding plasma FGF21 levels of 24 women were measured by ELISA [12 GDM (age: 26-47 years, BMI: 24.3-36.3 kg/m(2)) and 12 controls (age: 22-40 years, BMI: 30.1-37.0 kg/m(2))]. FGF21 levels in conditioned media were secretion from GDM and control human placental explants were also measured by ELISA. RESULTS: Glucose, HOMA-IR and circulating NEFA levels were significantly higher in women with GDM compared to control subjects. Plasma FGF21 levels were significantly higher in women with GDM compared to control subjects [234.3 (150.2-352.7) vs. 115.5 (60.5-188.7) pg/ml; P<0.05]. However, there was no significant difference in CSF FGF21 levels in women with GDM compared to control subjects. Interestingly, CSF/Plasma FGF21 ratio was significantly lower in women with GDM compared to control subjects [0.4 (0.3-0.6) vs. 0.8 (0.5-1.6); P<0.05]. FGF21 secretion into conditioned media was significantly lower in human placental explants from women with GDM compared to control subjects (P<0.05). CONCLUSIONS: The central actions of FGF21 in GDM subjects maybe pivotal in the pathogenesis of insulin resistance in GDM subjects. The significance of FGF21 produced by the placenta remains uncharted and maybe crucial in our understanding of the patho-physiology of GDM and its associated maternal and fetal complications. Future research should seek to elucidate these points.